Effect of fatigue and gender on running mechanics - Dutton, D. J.; Levy, M.; Lee, K. K.; Sidthalaw, S.; Smith, G. A (Medicine & Science in Sports & Exercise, 1997)
Video records of Olympic marathon runners (M = 12; F = 13) at the 33 and 41 km points of the 1992 Olympic marathon races in Barcelona were analyzed to assess the effect of fatigue on running kinematics and to allow comparison of those characteristics by gender. Both sites were on flat terrain. The greater running speeds of males (4.8 vs 4.1 m/sec) were due to greater stride length. The stride frequency was similar for both genders. Knee range of movement and peak angular velocity were significantly greater for females. Knee and ankle angles shifted to slightly more flexed positions as fatigue was incurred in both genders. Elite male and female runners differ slightly in running kinematics while modifying their movement patterns similarly as fatigue accumulates in a marathon race.